Pemantauan Paska Transplantasi Ginjal - Yuswanto Setyawan (Universitas Sam Ratulangi, 2023)
Kidney transplant recipients require unique medical care that includes attention not only to the function of the transplant itself, but also to common medical problems that are more prevalent, more atypical, and more severe in presentation than in the general population. Due to the successes of kidney transplantation, the estimated additional life-years gained from renal transplantation vary from 8 to 31 years. During the early phase, prevention of acute rejection and infection are the priority. After around 3–6 months, the priorities change to preservation of transplant function and avoiding the long-term complications of immunosuppressive medication (the medication used to suppress the immune system to prevent rejection). The potential complications discussed include heart disease, infection, cancer, bone disease and blood disorders. There is also a section on contraception and reproductive issues. In conclusion, the most important management of post kidney transplantation is prevention of acute rejection and opportunistic infections. Prognosis of kidney transplant recipient will worsen if both of the conditions mentioned occur. Keywords: kidney transplant recipients; post kidney transplantation; early phase prevention; long-term-complications Abstrak: Resipien transplantasi ginjal memerlukan perawatan medis khusus yang memerlukan perhatian tidak hanya pada fungsi transplantasi itu sendiri, tetapi juga pada masalah medis umum yang sering timbul, atipikal, umumnya dengan presentasi yang lebih parah daripada populasi umum. Transplantasi ginjal yang berhasil dapat menambah usia harapan hidup yang bervariasi, berkisar delapan hingga 31 tahun. Selama fase awal prioritas penanganan ialah reaksi penolakan akut dan pencegahan infeksi. Setelah 3-6 bulan paska trasnplantasi, prioritas ialah mempertahankan fungsi transplantasi dan menghindari komplikasi jangka panjang dari pengobatan imunosupresif (obat yang digunakan untuk menekan sistem kekebalan, untuk mencegah reaksi penolakan). Potensi komplikasi yang dibahas meliputi penyakit jantung, infeksi, kanker, penyakit tulang, kelainan darah, kontrasepsi dan masalah reproduksi. Simpulan kajian ini ialah penatalaksanaan paska transplantasi ginjal yang paling penting berupa pencegahan penolakan akut dan infeksi oportunistik, dimana prognosis resipien transplantasi ginjal akan memburuk jika kedua kondisi tersebut terjadi. Kata kunci: resipien transplantasi ginjal; pasca transplantasi ginjal; pencegahan tahap awal; komplikasi jangka panjang